Sustainable Synthesis of Diverse Privileged Heterocycles by Palladium-Catalyzed Aerobic Oxidative Isocyanide Insertion - Vlaar, Tjøstil; Cioc, Razvan C.; Mampuys, Pieter; Maes, Bert U. W.; Orru, Romano V. A.; Ruijter, Eelco (Angewandte Chemie International Edition, 2012)
O2 in, H2O out: Various diamines and related bisnucleophiles readily undergo oxidative isocyanide insertion with Pd(OAc)2 (1 mol %) as the catalyst and O2 as the terminal oxidant to give a diverse array of medicinally relevant N heterocycles. The utility of this highly sustainable method is demonstrated by a formal synthesis of the antihistamines astemizole and norastemizole.